1990
DOI: 10.1007/bf00264447
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence elements required for transcription initiation of the Schizosaccharomyces pombe ADH gene in Saccharomyces cerevisiae

Abstract: The roles of the TATA element and sequences near the mRNA initiation site in specifying the location of initiation sites in Saccharomyces cerevisiae were examined, using the Schizosaccharomyces pombe ADH gene. The importance of spacing was demonstrated by analysis of a series of deletions that removed from 8-50 bp between the TATA element and ATG translation initiation site of this gene. Primer extension mapping showed that increasing deletion length is associated with a progressive shift downstream in the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
2
42
0
Order By: Relevance
“…Importance of a pyrimidine-purine sequence at the start site It is known that prokaryotic and other eukaryotic RNA polymerases generally use a purine as the starting nucleotide of transcripts (18)(19)(20)(21) and there are indications that this may also be true for Pol III (22,23). In all of our CSE spacing mutants the initiation site nucleotide was a purine preceded by a pyrimidine.…”
Section: Introductionmentioning
confidence: 80%
“…Importance of a pyrimidine-purine sequence at the start site It is known that prokaryotic and other eukaryotic RNA polymerases generally use a purine as the starting nucleotide of transcripts (18)(19)(20)(21) and there are indications that this may also be true for Pol III (22,23). In all of our CSE spacing mutants the initiation site nucleotide was a purine preceded by a pyrimidine.…”
Section: Introductionmentioning
confidence: 80%
“…6). Examination of the sequence of the ADH1 and HIS3 start sites revealed that the ADH1 Ϫ38 and Ϫ37 sites and the ADH1 Ϫ28 and Ϫ27 sites reside within a CAAGC motif while the HIS3 Ϫ23 site is contained within the sequence CAGGC, both sharing homology with a PyAA/TPu proposed consensus sequence for S. cerevisiae RNAPII start sites (14,20,22). The suggestion that the differential sensitivity of these start sites to TFIIB mutations is due to sequence differences in the immediate vicinity of the sites was further supported by the demonstration that a T(Ϫ40)C substitution conferred decreased sensitivity of the ADH1 Ϫ38 and Ϫ37 sites to TFIIB mutations, whereas a G(Ϫ25)T substitution rendered the HIS3 Ϫ23 start site more sensitive (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The initial sequence comparisons and mutational analysis of a relatively small set of yeast mRNA genes helped define three related yeast start site consensus sequences, RRYRR, TCRA, and YA(A/T)R in the non-template strand, where the initiation site is underlined, Y is pyrimidine, and R is purine (12)(13)(14). Recently, an alignment of sequences flanking 4637 yeast transcription start sites has provided a more refined consensus sequence: A(A rich ) 5 NYA(A/T)NN(A rich ) 6 (15).…”
Section: Eukaryotes Rely On Rna Polymerase II (Rnap Ii)mentioning
confidence: 99%